Analisis Pernikahan Beda Agama Perspektif Hukum Islam Dan Hukum Positif (Studi Kasus Penetapan Pengadilan Negeri Surabaya Nomor 916/Pdt.P/2022/PN.Sby) - Muhammad Roni (Journal of Law and Islamic Law, 2023)
This study discusses interfaith marriage from the perspective of Islamic law and positive law, as well as an analysis of the judge's decision in the case of an interfaith marriage application in the Surabaya District Court's decision No. 916/Pdt.P/2022/PN.Sby, in this determination, the judge granted requests for interfaith marriages based on juridical facts in court, and in determining, the judge also exercised caution. Researchers use normative juridical research with the statutory, case study, comparative and conceptual approaches, then the data collected by researchers is obtained from various existing sources, such as books, journals, theses, judge's decisions, laws, and so on. Researchers used data reduction techniques to analyze, present, and conclude. The conclusions obtained from this study are as follows: Interfaith marriage, according to Islamic law, is prohibited as well as according to positive law, it also contradicts the provisions in the Marriage Law. Whereas the decision of the Surabaya District Court Number 916/Pdt.P/2022/PN.Sby is not in line with the provisions of Islamic law and positive law that in that decision, the judge granted the request for interfaith marriage in which the trial found the existing juridical facts and the judge also exercised caution in making such decisions.